Analisis Tingkat Penerimaan dan Penggunaan Sistem Informasi Manajemen Puskesmas Di Kabupaten Jember - Sedyo Pinerdi; Efri Tri Ardianto; Alinea Dwi Elisanti (Jurnal Manajemen Kesehatan Indonesia, 2020)
The Health Office (HE) in Jember District has conducted tests the operation of 40% Public Health Center Information System Management (SIMPUS). But from 20 public health centers (PHC), only 80% of the PHC ran it. The HE of Jember targets the end of 2019 SIMPUS will be fully operated in 50 PHC throughout the Jember district. The study aims to analyze the acceptance and use of technology systems in health center management by using the methods of the unified theory of acceptance and use of technology (UTAUT). The study examined variables of performance expectation, effort expectation, social impact, facilitating conditions, behavioral interest, and behavior of SIMPUS users. This study was analytic research. The data analysis technique used path analysis. The result explains the performance expectation is effected to the behavioral interest (t-value: 2,9); effort expectation is effected to the behavioral interest (t-value:1,01); social impact is effected to the behavioral interest (t-value: 9,47); facilitating conditions is effected to the user's behavioral (t-value:4,67); behavioral interest is effected to the user's behavior (t-value:8,54). Important for Health Office to maintain SIMPUS quality as well as to frequent SIMPUS updates in order to increase SIMPUS behavior